Partisipasi Masyarakat dalam Proses Penyusunan Peraturan Daerah (Studi Kasus Peraturan Daerah Provinsi Bengkulu Nomor 12 Tahun 2013 tentang Perbaikan Gizi) - Alfina Hidayati; Wahyu Sulistiadi (Center for Health Policy and Management, 2017)
ABSTRACTBackground: There are some problems concerning the quality of legislation, and the involvement of community participation in the process of drafting and design of a regulation being in the concern.Purpose: The purpose of this study to obtain information on the public participation in the formulation of the Regional Regulations.Method: This is a qualitative research that conduct analysis based on the stages in the preparation of Regulation No. 12 of 2013, namely Definition, Aggregation, Organitation, Representation, Agenda Setting, Formulation and Legitimation last stage.Result: The process of drafting Regulation No. 12 of 2013 is not a meaningful public participation, except in some seminar were the number of participants is limited. The availability of academic paper is a starting material containing ideas of urgency, approach, scope and substance of a regional regulation.Conclusion: It is advisable to increase community participation in every decision-making process, which can be done with advocacy to community groups that carried out by universities, community organizations and local government. There should be local regulations that regulate and ensure people’s participation in any decision-making process, as well as the need to support it with adequate human resources, adequate funding and adequate time so that the academic paper worthy of reference in the process of drafting a regional regulation. Keywords: Public Participation, Academic Manuscript, Regional RegulationABSTRAKLatar belakang: Permasalahan produk legislasi yang menyangkut kualitas, maupun pelibatan partisipasi masyarakat di dalam proses penyusunan dan perancangan suatu Perda sedang menjadi sorotan.Tujuan: Tujuan penelitian ini untuk memperoleh informasi mengenai partisipasi masyarakat dalam proses penyusunan Peraturan Daerah menggunakan pendekatan kualitatif.Metode: Berdasarkan analisis bahwa tahapan-tahapan dalam penyusunan Perda no 12 tahun 2013 telah melakukan semua tahapan dari tahap Definition, Aggregation, Organitation, Representation, Agenda Setting, Formulation dan terakhir tahapLegitimation.Hasil: Proses penyusunan Perda No 12 tahun 2013 belum melibatkan partisipasi masyarakat kecuali dalam seminar uji publik yang jumlah pesertanya terbatas. Kedudukan naskah akademik merupakan bahan awal yang memuat gagasan-gagasan tentang urgensi, pendekatan, ruang lingkup dan materi muatan suatu Peraturan Daerah.Kesimpulan: Disarankan untuk meningkatkan partisipasi masyarakat dalam setiap proses penyusunan Perda dapat dilakukan dengan advokasi kepada kelompok masyarakat yang dilakukan oleh Perguruan Tinggi, organisasi masyarakat maupun pemerintahan daerah Provinsi Bengkulu sendiri, memiliki produk hukum daerah yang mengatur dan menjamin partisipasi masyarakat dalam setiap proses penyusunan Perda, serta perlu dukunganan sumber daya manusia yang memadai, dana yang cukup dan waktu yang lebih banyak sehingga Naskah Akademik yang dihasilkan layak dijadikan acuan dalam proses penyusunan suatu peraturan daerah. Kata kunci: Partisipasi Masyarakat, Naskah Akademik, Peraturan Daerah